DEVELOPING DATABASES FOR AN INTELLIGENT ENVIRONMENT - Ostanakulov Xikmatillo; Abduganiyev Abdugaffor; Shokirov Shokhrukh (Scientific Impulse, 2024)
Creating databases for an intelligent environment involves designing and implementing robust data structures to support the seamless functioning of smart systems. This abstract explores the intricacies of developing databases tailored for environments where intelligence is a key factor. The focus is on optimizing data storage, retrieval, and processing to enhance the efficiency of intelligent systems. Addressing challenges such as real-time data updates, interoperability, and scalability, this endeavor aims to foster a foundation for the next generation of intelligent environments. The abstract delves into key considerations, methodologies, and potential applications, highlighting the pivotal role of well-crafted databases in shaping the intelligence of contemporary technological ecosystems.